Land as a Fundamental Right: a Cautionary Tale - Farran, Sue (Victoria University of Wellington Law Review, 2009)
The article discusses the importance of land rights in the South Pacific for securing the enjoyment of other civil, political, economic, and social rights in the Pacific focusing especially on Vanuatu as a paradigm. The infringement of land rights and the abuse of natural resources in the Pacific have a long history and the consequences on human rights on the whole are severe. The article argues that current constitutional provisions do not go far enough to ensure that land rights are protected and consequently to ensure the enjoyment human rights as a whole.